European integration and the welfare state(s) in Europe - Falkner, Gerda (Vienna, 2009)
"This paper summarizes the state-of-the-art on European social policy integration. It summarises the controversy over the ‘social dimension of European integration’, which has been ongoing ever since the founding fathers of European integration in 1957 agreed that the economies should be integrated basically without social regulation to counterbalance liberalisation effects. It presents the historical development of EU social policy as well as criteria for evaluating the state of “social Europe” and finally discusses how the EU is impacting on different types of welfare states. The argument is that the EU contributes to framework conditions that promote more ‘bounded varieties of welfare’ in Europe. In other words, it is held that there will be a more restricted variety, oscillating within limits that are directly or indirectly imposed or reinforced by European integration."